Impact of the use of information technologies in precision agriculture - Cortez Vásquez, Augusto Parcemón (2023)
In recent years, the new approaches to the study of agriculture in the world face serious problems, and have begun to take into account global processes and their effects, such as the contamination of water resources and soil degradation. Peru cannot escape this problem, especially at this time when the situation is complicated due to the occurrence of phenomena such as climate change that manifests itself in variables such as increased temperature, variation in precipitation, soil degradation , variables that put food security at risk. As a consequence, there is a reduction in the world food supply and consequently an increase in prices (Latella, 2020) (Ramirez, 2010). The changes that are taking place at a global, regional and local level, caused by climate change, have had a substantial impact on the agricultural sector, causing concern not only for farmers, but also for economists, environmentalists and even governments (Viguerra, 2017).  The objective of this project is to carry out a bibliographical review of existing technologies that serve as a tool for farmers, which promotes technological innovation in the different processes related to agriculture.